Development of the Independence of The Community of People with Disabilities Based on Batik Ciprat Msmes at Rumah Harapan Karangpatihan Village - Adib Khusnul Rois Adib Khusnul; Anip Dwi Saputro; Alip Sugianto; Happy Susanto; Ayok Ariyanto; Devid Dwi Erwahyudin; Sigit Dwi Laksana; Nichita Arzeti Mahardika (Society : Jurnal Pengabdian Masyarakat, 2025)
Poverty that occurs in Karangpatihan is one of the special concerns for the village government, especially for the people of the Unable, there are several kinds of economic development that have been carried out, namely by means of goat farming programs, catfish farming, free-range chicken farming and others. In addition to raising livestock for Tunagrahita residents, they also develop mat crafts and make splash batik typical of the residents of Tunagrahita Balong Ponorogo, this splash batik is an income program for Tunagrahita residents. Splash batik crafts in Karangpatihan Village have been running for more than 7 years, this craft is carried out at the Rumah Harapan of Karangpatihan Village, Balong Ponorogo which is carried out by people with disabilities with disabilities. This splash batik has many models with various patterns produced, this splash batik can be bought or ordered at the Karangpatihan Village Hope house with various prices of Rp.160,000 per piece and so on splash batik that has been made by the disabled becomes the flagship product of Karangpatihan Balong village Ponorogo Finished splash batik is then collected at the Karangpatihan Balong village hope house to be displayed. Splash batik is the mainstay product of the Balong ponorogo homeless community which is managed by a team of volunteers from the Rumah Harapan volunteers.